Electrochemical properties of spinel LiMn2O4 cathode material prepared by a microwave-induced solution flameless combustion method. (June 2019) - Tian, Liang; Su, Changwei; Wang, Yan; Wen, BiXia; Bai, Wei; Guo, Junming
Abstract: Spinel LiMn2 O4 powders have been hyper-rapidly produced by a microwave-induced solution flameless combustion method (MISFC) for 5 min using lithium nitrate, manganese acetate and nitric acid as raw materials. The XRD data indicate that the phase composition is severely affected by the molar ratio of NO3 − :Ac − (N:A). The LiMnO2 and Mn3 O4 impurities successively disappear along with the increase of the N:A ratio. The pure LiMn2 O4 product prepared at 1:1 is composed of polyhedral crystals with submicron size. Its initial discharge specific capacity reaches 114.4 mAh g −1 at 1C and there is still 52.0 mAh g −1 at the 1000 th cycle. The XRD and TEM data suggest that the sample showed excellent stability during long cycles. Highlights: A new rapid-preparation method (MISFC) of LiMn2 O4 cathode materials is proposed. Its crystal structure can be still retained after 1000 cycles at 1C rate. It has a higher initial discharge specific capacity and a good capacity retention rate at 1C.